Pengaruh Durasi Sakit dan Dosis Kumulatif Prednison terhadap Fungsi dan Geometri Ventrikel Kiri pada Anak dengan Sindroma Nefrotik - Muhammad Heru Muryawan; Irma Rezky Ratu; Anindita Soetadji (Medica Hospitalia : Journal of Clinical Medicine, 2017)
Background: Nephrotic syndrome is a chronic disease that often occurs in children. Treatment with prednison as a first line treatment in nephrotic syndrome plays a role in the process of remodeling and left ventricular hypertrophy. Prevalence of LVH among CKD patients is 34 - 78%. The presence of LVH increases the risk of mortality and morbidity of cardiovascular disorders, so its recomended to determine geometry of left ventricle to see the systolic and diastolic function. Objective: To determine the effect of duration of illness and cumulative prednison dossage on geometry and left ventricular function children with nephrotic syndrome. Methods: A cross sectional study of 27 children between 1 -18 years was conducted in Kariadi hospital, Semarang. Subjects were enrolled by consecutive sampling. The cumulative dose of prednison was calculated based on overall dose received during treatment untill echocardiography were done. Geometric parameter and left ventricular function were determined by M – mode echocardiography. Data were analyzed using bivariate analysis. Results: There is a significant difference between cumulative prednison dossage and left ventricular geometry (p=0.001). Duration of illness (p= 0.60) and cumulative prednison dossage (p=0.44) were not significantly associated with diastolic ventricular function. Conclusion: Cumulative prednison dossage was significantly associated with concentric tipe left ventricular geometry and there is no association with duration of illness. There is no effect of duration of illness and cumulative prednison dossage in diastolic ventricular function. Keywords: Nephrotic syndrome, prednison, left ventricular geometry